Exploring Strategies to Facilitate Diverse Student Learning Styles in Social Science Education - Fawziah Zahrawati B; Andi Aras (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
The Merdeka curriculum promotes differentiated learning for diverse student learning styles. This research exploring implementing the Merdeka Curriculum and teachers' strategies and challenges in facilitating diverse student learning styles. The research method was qualitative and conducted at UPT SMA Negeri 4 Parepare. School principals, social science teachers, and students served as informants. Data collection techniques include interviews, observation, and documentation. Triangulation of methods and sources is used to obtain data validity. Analysis of the data followed Miles and Huberman's stages. The Merdeka Curriculum is not fully implemented at all grade levels, according to this research. Social science teachers use strategies to accommodate diverse learning styles, such as identifying styles, using different methods, group learning, varied assessments, technology, reflection, and personalization. Teachers face the challenge of adapting various learning styles in the Merdeka Curriculum. Teachers should generate innovative ideas for the Pancasila Student Profile. Teachers need to prepare tools and materials for different learning styles. Teachers should understand the diversity of students' learning styles and become skilled facilitators in exploring their potential. The findings of this research offer strategies for teachers to implement the Merdeka Curriculum.Keywords: Differentiated learning; learning styles; teacher strategies; the Merdeka Curriculum.